Metallo-β-lactamase-mediated resistance among clinical carbapenem-resistant Pseudomonas aeruginosa isolates in northern Iran: A potential threat to clinical therapeutics - Abdol Ahad Dogonchi; Ezzat Allah Ghaemi; Abdollah Ardebili; Sajjad Yazdansetad; Abazar Pournajaf (Tzu Chi Medical Journal)
Objective: Carbapenems are effective agents to treat multidrug-resistant (MDR) strains of bacteria, including Pseudomonas aeruginosa. However, there is a potential threat of emergence of carbapenem-resistant P. aeruginosa (CRPA). The aim of this study was to determine antibiotic susceptibility patterns and metallo-beta-lactamase (MBL)-mediated resistance in clinical P. aeruginosa isolates. Materials and Methods: Different clinical specimens were subjected to conventional culture-based identification of P. aeruginosa. Antimicrobial susceptibility patterns and MBL production were evaluated using the Kirby-Bauer and combined double-disk synergy test methods, respectively. Multiplex polymerase chain reaction was performed to investigate the presence of the blaIMP, blaVIM, blaNDM, blaSPM, and blaSIMgenes. Results: A total of 71 clinical P. aeruginosa isolates were recovered, of which 28.17% were identified as CRPA. The most active antibiotics were colistin and polymyxin B (92.96% susceptibility to each). A total of 35% and 50% of CRPA isolates were MDR and extensively drug-resistant (XDR), respectively. MBL activity was shown in 20% of CRPA. A total of 90%, 40%, and 5% of CRPA isolates harbored the blaIMP, blaVIM, and blaNDMgenes, respectively. No correlation was found between the MBL-encoding genes of P. aeruginosa and patient characteristics. Conclusion: Although the prevalence of CRPA in our therapeutic centers was relatively low, this rate of carbapenem resistance reflects a threat limiting treatment choices. A high prevalence of MDR/XDR phenotypes among the MBL-producer isolates suggests the need for continuous assessment of antimicrobial susceptibility and surveillance of antibiotic prescription. In addition, infection control measures are needed to prevent further dissemination of these organisms.